(untitled) (Global Journal of Science Frontier Research, 2018)
The unification of Newton’s/ Einstein’s Gravity and Quantum Mechanics is truly a focus of science with great promise for our increased understanding of the cosmos. So to find a theory that explains the connection of these two concepts of our reality is indeed an exciting prospect. This paper attempts to do that and explain how life is a contributing force which appears to be an essential part of the complete picture. It may require further reading about the details of the evolving Cosmic Dark Matter Fractal Field Theory (CDMFFT) to better understand the full concept but those links are provided to previous foundational work published by GJSFR for your review. The other theories that attempt to unify gravity and quantum mechanics such as String Theory have completely left out the explanation of the Life Force and its connection to the unification of gravity and quantum mechanics.